Femtosecond laser etching of dental enamel for bracket bonding - Kabas, Ayse Sena; Ersoy, Tansu; Gulsoy, Murat; Akturk, Selcuk (SPIE-Intl Soc Optical Eng, 2013)
The aim is to investigate femtosecond laser ablation as an alternative method for enamel etching used before bonding orthodontic brackets. A focused laser beam is scanned over enamel within the area of bonding in a saw tooth pattern with a varying number of lines. After patterning, ceramic brackets are bonded and bonding quality of the proposed technique is measured by a universal testing machine. The results are compared to the conventional acid etching method. Results show that bonding strength is a function of laser average power and the density of the ablated lines. Intrapulpal temperature changes are also recorded and observed minimal effects are observed. Enamel surface of the samples is investigated microscopically and no signs of damage or cracking are observed. In conclusion, femtosecond laser exposure on enamel surface yields controllable patterns that provide efficient bonding strength with less removal of dental tissue than conventional acid-etching technique.
Keywords: Orthodontic Brackets; Lasers; Dental Etching; Dental Bonding; Temperature; Animals; Cattle; Dental Enamel; Shear Strength